Exploring virtual world innovations and design through learner voices - Gregory, S.; McDonald, M.; O’Connell, J.; Jegathesan, J.J.; Stokes-Thompson, F.; Sim, J.; Hearns, M.; Gregory, B.; Nikolic, S.; Butler, D.; McGrath, N.; Sukunesan, S.; et al. (2016)
© 2016 Deakin University. All Rights Reserved. Student voice has played a big role in shaping the development and measure of success/failure of virtual worlds in education. Data on past and ongoing educational uses and contexts of use of virtual worlds and associated student feedback was gathered via a survey of educational researchers specialising in virtual worlds. Introduced are a range of specific uses that provide the source of and context for student feedback. Ten major themes emerged from student voices that highlight strengths and weakness and point the way forward for both educators and the students themselves. Positive feedback highlighted experiences of both pedagogical design and the ability of the technology to support it. Negative feedback revolved around technical problems, seen as hampering the effectiveness of student learning experiences. Student voice regarding virtual worlds is both positive and rewarding, and commending of staff who have dedicated their time and effort to transform the learning experience.